2005
DOI: 10.1002/qsar.200420105
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Preparation of a Library Based on a Phenylalanine Scaffold

Abstract: A convenient strategy (preliminary study, preproduction and production) for the solidphase preparation of a library using 4-iodophenylalanine as a scaffold is described. The aromatic ring was first modified via the Suzuki reaction and the amino position was subsequently derivatized into amides, sulfonamides, amines, carbamates and ureas. The scope and limitations of all of the reactions carried out in parallel are discussed. The solid-phase synthesis of a library of 315 individual compounds was attempted by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Instead of synthesizing a new peptide with Ala 1 being introduced under the Boc form, we removed the Fmoc moiety and replaced it with a Boc group using the (Boc) 2 O anhydride (Scheme ). Moreover, a recent study reported that H 2 N-Phe( p I)-OH anchored to a Wang linker was not totally stable to Suzuki conditions because of the base-catalyzed hydrolysis . Thus, the reaction was attempted a second time but with a Boc protection approach at the N-terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Instead of synthesizing a new peptide with Ala 1 being introduced under the Boc form, we removed the Fmoc moiety and replaced it with a Boc group using the (Boc) 2 O anhydride (Scheme ). Moreover, a recent study reported that H 2 N-Phe( p I)-OH anchored to a Wang linker was not totally stable to Suzuki conditions because of the base-catalyzed hydrolysis . Thus, the reaction was attempted a second time but with a Boc protection approach at the N-terminus.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, cyclic peptides, either naturally occurring or synthetically constructed, and C -modified peptides have proven to be excellent molecular scaffolds for design purposes . In this field of research, phenylalanine has become an important pharmacophore in SAR studies because of the key role that plays eliciting intrinsic activity in compounds that contain this amino acid . Thus, the nonpolar nature and steric bulkiness of its side chain is responsible for crucial hydrophobic interactions in molecular recognition processes .…”
mentioning
confidence: 99%
“…The preparation of the carbamate derivatives 10 was attempted under various conditions via activation of the alcohol with Disuccinimidyl Carbonate (DSC) (entries 1 -5, Table 4) [9].…”
Section: Resultsmentioning
confidence: 99%